Zirconium-based fuel cladding surface corrosion-resistant interface integrated ZrxO / SiC multilayer composite coating and preparation method thereof
By growing ZrxO oxide film on the surface of zirconium-based fuel cladding and depositing SiC multi-layer composite coating, the corrosion problems of zirconium-based materials in high-temperature and high-pressure water environment and the brittleness of SiC coating are solved, and the high resistance of zirconium-based fuel cladding is achieved Corrosion, wear resistance and accident tolerance.
Patent Information
- Application Number
- CN202411631040.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-15
AI Technical Summary
Zirconium-based fuel cladding is prone to corrosion in high-temperature and high-pressure water environments, resulting in boil-like corrosion and hydrogen explosion accidents. The existing SiC coating is prone to cracking and failure.
By growing ZrxO oxide film in situ on the surface of zirconium-based fuel cladding, combined with SiC ion sputtering cleaning and multi-layer alternating deposition technology, an integrated interface ZrxO/SiC multi-layer composite coating is built to enhance interface adaptability and strong toughness.
It improves the long-term and stable service performance of zirconium-based fuel cladding, enhances the corrosion resistance and wear resistance of the surface, reduces the chance of brittle cracking, and realizes the accident fault tolerance function.
Smart Images

Figure CN119433414A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials and surface engineering, and specifically relates to a zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x O / SiC multilayer composite coating and preparation method thereof. Background Art
[0002] Zirconium-based materials are currently the main nuclear fuel cladding materials used in pressurized water reactor nuclear power plants, mainly based on their good "nuclear properties", such as low neutron absorption cross-section and resistance to neutron irradiation. However, the application under working conditions shows that the corrosion of zirconium-based materials in high-temperature and high-pressure water is still a major hidden danger restricting its long-term stable service. Especially under accident conditions, zirconium-based cladding is very prone to nodular corrosion, which in turn causes thinning of the tube wall and causes fractures. What is more serious is that the exothermic reaction of hydrogen evolution from zirconium water in high-temperature steam will further lead to serious hydrogen explosion accidents. The use of functional coating materials for surface protection of zirconium-based materials is currently recognized as an important means to solve the shortcomings of zirconium-based materials in high-temperature and high-pressure water environments, and is also one of the important directions for the development of new accident-tolerant fuel systems.
[0003] SiC material has excellent high temperature performance, can still maintain high bonding strength at high temperature, small high temperature deformation, low thermal expansion coefficient, good chemical stability and thermal stability. Especially in the nuclear field, SiC material has a small neutron absorption cross section, good irradiation dimensional stability, and high thermal conductivity. In addition, the higher surface hardness makes it better resistant to grid scratches and micro-wear, and is very suitable as a surface protective coating for existing zirconium-based fuel cladding. However, the current application of SiC as a coating material on the surface of zirconium-based alloys still has the following problems. First, the commonly used coating preparation method is mainly chemical vapor deposition. The preparation temperature of this technology is higher than 1000°C, which is obviously not suitable for surface treatment of zirconium-based alloys. Second, compared with zirconium-based materials, SiC materials have higher hardness and brittleness. When deposited on the surface of zirconium-based materials as coating materials, the interface thermal mismatch is particularly significant. It is very easy to induce interface microcracks under external stress. Coupled with its own high brittleness, the brittle cracking failure tendency of the coating is particularly obvious. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x Preparation method of O / SiC multilayer composite coating. The present invention in situ grows Zr on the surface of zirconium-based fuel cladding by oxidation. xO oxide film is formed by combining with deposition to form a SiC multilayer composite coating, and a corrosion-resistant, wear-resistant integrated accident-tolerant composite coating is constructed on the surface of nuclear zirconium-based fuel cladding, which enhances the interface adaptability between the substrate and the coating, and simultaneously improves the strength and toughness of the coating while ensuring the surface hardness of the coating. The long-term stable service performance of the zirconium-based fuel cladding is improved, and the problem of easy cracking and failure of the existing SiC coating on the surface of zirconium alloy is solved.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x The method for preparing an O / SiC multilayer composite coating is characterized in that the method comprises the following steps:
[0006] Step 1: Zr x Preparation of O oxide film: The zirconium-based fuel cladding is surface pickled and rinsed with deionized water to remove surface oxides and attached pollutants, and then pre-oxidized after dehydration and drying. Zr with a gradient transition structure is in situ grown on the surface of the zirconium-based fuel cladding. x O oxide film;
[0007] Step 2: Ar plasma sputtering activation: Place the pre-oxidized zirconium-based fuel cladding in step 1 in a vacuum vapor deposition device and control the background vacuum to be better than 5×10 -3 Pa, the temperature does not exceed 400 ° C, and then Ar gas is introduced, and Ar plasma generated by Ar gas glow discharge is used for sputtering cleaning to clean and eliminate dust and other debris adsorbed by static electricity on the surface and activate the surface;
[0008] Step 3, SiC ion sputtering cleaning: Turn on the SiC sputtering target source, and under the action of high pulse bias, use SiC ions generated by the SiC target source to perform SiC ion sputtering cleaning on the surface of the zirconium-based fuel cladding after the Ar plasma sputtering cleaning in step 2;
[0009] Step 4: Deposition of SiC composite coating: Under the action of low pulse bias, a multi-layer SiC composite coating is alternately deposited on the surface of the zirconium-based fuel cladding cleaned by SiC ion sputtering in step 3, thereby obtaining a surface with a gradient transition structure Zr x Zirconium-based fuel cladding with O / SiC multilayer composite coating.
[0010] The present invention first pre-oxidizes the zirconium-based fuel cladding, and in-situ grows Zr on the surface of the zirconium-based fuel cladding. x O oxide film, and then alternately deposited to form a multilayer SiC composite coating. x O oxide film serves as a gradient buffer layer between the zirconium-based fuel cladding substrate and the surface SiC composite coating, achieving a non-interface transition from the substrate to the surface ceramic coating. xThe difference in thermal mismatch between the interface of the O oxide film and the surface SiC composite coating is small, which is beneficial to improving the interface bonding strength between the surface SiC composite coating and the substrate, and improving the application performance of the SiC coating on the surface of the zirconium alloy. At the same time, the present invention uses SiC ion sputtering cleaning, uses the bombardment of high-energy SiC to strengthen the interface to construct a low-stress, densified interface, combines multiple alternating depositions, and uses multi-cycle cyclic deposition to intermittently increase the SiC ion energy to interrupt the continuous growth trend of SiC grains, improve the structural density of the SiC composite coating, and construct a SiC composite coating system with a multi-layer structure. Under the premise of ensuring the surface hardness of the coating, the toughness of the coating is improved, the probability of brittle cracking is reduced, and the defects of large SiC brittleness are effectively alleviated, so as to achieve the simultaneous improvement of the strength and toughness of the surface SiC coating.
[0011] The above-mentioned zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x The preparation method of O / SiC multilayer composite coating is characterized in that the pre-oxidation in step 1 is carried out in an oxygen-containing atmosphere or in high-temperature and high-pressure steam. The pre-oxidation conditions in high-temperature and high-pressure steam are: pre-oxidation for 72 hours under high-temperature steam conditions of 400°C±3°C and 10.3MPa±0.7MPa in an autoclave. This pre-oxidation process can directly grow Zr in situ on the surface of the zirconium-based fuel cladding. x O oxide film, forming a gradient transition without interface and building an integrated interface structure.
[0012] The above-mentioned zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x The preparation method of O / SiC multilayer composite coating is characterized in that during the Ar plasma sputtering cleaning in step 2, Ar gas is used to adjust the vacuum value in the vacuum vapor deposition equipment to 3Pa~50Pa, and the pulse bias voltage is 500V~1500V, the duty cycle is 30%~80%, and the time is 7min~15min.
[0013] The above-mentioned zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x The method for preparing an O / SiC multilayer composite coating is characterized in that, during the SiC ion sputtering cleaning in step three, the pulse bias voltage is 500V to 1000V and the time is 2min to 5min.
[0014] The above-mentioned zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x The method for preparing an O / SiC multilayer composite coating is characterized in that the deposition of the SiC composite coating in step 4 comprises the following steps:
[0015] Step 401, preparation of SiC pre-deposition layer: maintaining the on state of SiC sputtering target source unchanged, reducing the pulse bias voltage, and preparing SiC pre-deposition layer on the surface of zirconium-based fuel cladding cleaned by SiC ion sputtering in step 3;
[0016] Step 402 , preparation of SiC thickening layer: reducing the pulse bias voltage, and depositing a SiC thickening layer on the surface of the SiC pre-deposition layer of the zirconium-based fuel cladding in step 401 .
[0017] The present invention adopts high pulse bias voltage to increase the energy of deposited ions to obtain a denser SiC pre-deposition layer structure, and then reduces the pulse bias voltage to promote a large amount of ion deposition, thereby achieving thickening of the SiC composite coating and improving deposition efficiency; at the same time, by successively reducing the energy of deposited ions, it is helpful to eliminate deposition stress and further improve the quality of the SiC composite coating.
[0018] The above-mentioned zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x The preparation method of O / SiC multilayer composite coating is characterized in that the pulse bias voltage used in the preparation of the SiC pre-deposition layer in step 401 is 300V~500V, the time is 5min~10min, and the vacuum degree is 0.1Pa~1Pa; the pulse bias voltage used in the preparation of the SiC thickening layer in step 402 is 50V~100V, and the vacuum degree is 0.1Pa~1Pa.
[0019] The above-mentioned zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x The method for preparing an O / SiC multilayer composite coating is characterized in that the SiC pre-deposition layer preparation process in step 401 and the SiC thickening layer preparation process in step 402 are repeated alternately multiple times to form a SiC composite coating with a multilayer structure.
[0020] The above-mentioned zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x The method for preparing the O / SiC multilayer composite coating is characterized in that an auxiliary plasma source is added to the vacuum vapor deposition equipment described in step 2. By adding the auxiliary plasma source to the vacuum vapor deposition equipment to complete the subsequent sputtering and deposition processes, the sputtering rate of the SiC target source and the coating deposition efficiency are improved, thereby improving the interface bonding force between the body and the coating and enhancing the overall performance of the coating.
[0021] At the same time, the present invention also discloses a zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr -x The O / SiC multilayer composite coating is characterized in that it is prepared by the above method.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] 1. The present invention in situ grows Zr by pre-oxidation on the surface of zirconium-based fuel cladding x O oxide film, constructing a gradient channel from the substrate to the surface SiC coating, realizing the interface-free transition from the substrate to the surface SiC coating, enhancing the interface adaptability between the substrate and the coating, and improving the degree of bonding between the two; at the same time, the present invention constructs a SiC composite coating system with a multi-layer structure through SiC ion bombardment strengthening and multi-layer alternating deposition, and improves the toughness of the coating year-on-year while ensuring the surface hardness of the coating, thereby obtaining a zirconium-based fuel cladding surface interface integrated Zr with excellent corrosion resistance, wear resistance and accident fault tolerance. x O / SiC multilayer composite coating improves the long-term stable service performance of zirconium-based fuel cladding.
[0024] 2. In the structural design and preparation of the surface SiC coating of the present invention, an interface ion pre-strengthening process is introduced to artificially construct a low-stress, densified and strengthened interface. At the same time, the continuous growth of SiC grains is interrupted periodically through alternating deposition to improve the density of the composite coating, thereby ensuring that a multi-layered SiC composite coating is obtained through multi-cycle cycles, thereby achieving a simultaneous improvement in the strength and toughness of the SiC composite coating.
[0025] 3. The interface integrated Zr constructed on the surface of the zirconium-based fuel cladding of the present invention x O / SiC multilayer composite coating contains in-situ grown dense Zr x O oxide film and SiC multilayer composite coating, using the in-situ growth of Zr on the substrate x O and then to the gradient composite structure of the SiC composite coating on the surface, which reduces the thermal mismatch and interface thermal resistance between the base metal and the ceramic coating, avoids the "thin ice effect" of brittle fracture of the soft metal (Zr) / hard coating (SiC) system, and at the same time, with the help of the high corrosion resistance, high thermal conductivity and high hardness of the SiC composite coating, the surface corrosion resistance and wear resistance of the zirconium-based fuel cladding under normal and accident conditions are improved, and the fault tolerance of the zirconium-based fuel cladding under accident conditions is optimized.
[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The Zr formed on the surface of the Zr-4 zirconium alloy cladding in Example 1 of the present invention x Surface morphology of O / SiC multilayer composite coating.
[0028] Figure 2 The Zr formed on the surface of the Zr-4 zirconium alloy cladding in Example 1 of the present invention x Cross-sectional morphology of O / SiC multilayer composite coating.
[0029] Figure 3The Zr formed on the surface of the Zr-4 zirconium alloy cladding in Example 1 of the present invention x Surface wear scar morphology of O / SiC multilayer composite coating after 3N load and 30min of wear.
[0030] Figure 4 The Zr formed on the surface of the Zr-4 zirconium alloy cladding in Example 1 of the present invention x Cross-sectional morphology of O / SiC multilayer composite coating after high-temperature steam corrosion at 1200℃ for 2h. DETAILED DESCRIPTION
[0031] Example 1
[0032] This embodiment includes the following steps:
[0033] Step 1: Zr x Preparation of O oxide film: The Zr-4 zirconium alloy cladding is pickled and rinsed with deionized water to remove surface oxides and attached pollutants, and then pre-oxidized after dehydration and drying. Zr with a gradient transition structure is in situ grown on the surface of the Zr-4 zirconium alloy cladding. x O oxide film; the pre-oxidation is pre-oxidation for 72 hours under high temperature steam conditions of 400°C ± 3°C and 10.3MPa ± 0.7MPa in an autoclave;
[0034] Step 2: Ar plasma sputtering activation: After cleaning and drying the pre-oxidized Zr-4 zirconium alloy cladding in step 1, place it in a vacuum vapor deposition device with an auxiliary plasma source, and vertically hoist it on the workpiece rack so that it can rotate and revolve synchronously at the same time. The background vacuum is controlled to be 5×10 -3 Pa, the temperature is 220 ° C, and then Ar gas is introduced, the vacuum value in the vacuum vapor deposition equipment is adjusted to 10Pa, and the pulse bias is 1000V, the duty cycle is 80%, and the Ar plasma generated by Ar gas glow discharge is used for sputtering cleaning for 10 minutes to clean and eliminate dust and other debris adsorbed by static electricity on the surface and activate the surface;
[0035] Step 3, SiC ion sputtering cleaning: reduce the Ar gas flow rate to adjust the vacuum value in the vacuum vapor deposition equipment to 0.3 Pa, turn on the SiC sputtering target source, control the power of the SiC sputtering target source to 5 kW, and use the SiC ions generated by the SiC target source sputtering to perform SiC ion sputtering cleaning on the surface of the Zr-4 zirconium alloy cladding after Ar plasma sputtering cleaning in step 2 for 5 minutes under the conditions of a pulse bias of 500 V and a duty cycle of 80%;
[0036] Step 4: Deposition of SiC composite coating: Under the action of low pulse bias, a multi-layer SiC composite coating is alternately deposited on the surface of the Zr-4 zirconium alloy cladding cleaned by SiC ion sputtering in step 3, thereby obtaining a surface with a gradient transition structure Zr x O / SiC multilayer composite coating Zr-4 zirconium alloy cladding; the SiC composite coating deposition comprises the following steps:
[0037] Step 401, preparation of SiC pre-deposition layer: maintaining the SiC sputtering target source on state unchanged, and the power of the SiC sputtering target source is 5kW, reducing the pulse bias voltage to 400V, controlling the duty cycle to 80%, and the vacuum degree to 0.3Pa, and pre-depositing the SiC pre-deposition layer on the surface of the Zr-4 zirconium alloy cladding cleaned by SiC ion sputtering in step 3 for 7 minutes;
[0038] Step 402, preparation of SiC thickening layer: reducing the pulse bias voltage to 80V, controlling the duty cycle to 80%, the vacuum degree to 0.3Pa, depositing the SiC pre-deposition layer on the surface of the Zr-4 zirconium alloy cladding in step 401 for 60min, and preparing a SiC thickening layer with a thickness of 2μm;
[0039] The SiC pre-deposition layer preparation process in step 401 and the SiC thickening layer preparation process in step 402 were repeated alternately 5 times each to form a SiC composite coating having a 6-layer periodic structure and a total thickness of 12 μm.
[0040] Figure 1 and Figure 2 They are respectively the Zr formed on the surface of the Zr-4 zirconium alloy cladding in this embodiment. x Surface morphology and cross-sectional morphology of O / SiC multilayer composite coating. Figure 1 and Figure 2 It can be seen that the Zr formed on the surface of the Zr-4 zirconium alloy cladding in this embodiment x The surface of the O / SiC multilayer composite coating is uniform and compact. Its cross-sectional structure shows that due to the presence of the SiC pre-deposition layer, the overall structural consistency of the SiC composite coating is very significant. There is no obvious multilayer composite structure. x The thickness of the O / SiC multilayer composite coating is about 15 μm.
[0041] The Zr formed on the surface of the Zr-4 zirconium alloy cladding in this embodiment x The sliding wear test of O / SiC multilayer composite coating was carried out. Under the test conditions of 3N external load, φ6mm stainless steel ball of friction pair and wear linear velocity of 1m / s, the surface morphology after 30min of wear time is as follows: Figure 3 As shown. Figure 3It can be seen that the surface of the composite coating presents a uniform wear state, without obvious abrasive wear, coating peeling and other phenomena.
[0042] The Zr formed on the surface of the Zr-4 zirconium alloy cladding in this embodiment x The O / SiC multilayer composite coating was subjected to a 2h steam corrosion test in 1200℃ high temperature steam. The cross-sectional morphology of the coating after corrosion is shown in Figure 2. Figure 4 As shown. Figure 4 It can be seen that the composite coating has a complete surface, the Zr-4 zirconium alloy cladding substrate has no oxidation corrosion, and the composite coating has a significant protective effect.
[0043] Example 2
[0044] This embodiment includes the following steps:
[0045] Step 1: Zr x Preparation of O oxide film: The Zr-4 zirconium alloy cladding is pickled and rinsed with deionized water to remove surface oxides and attached pollutants, and then pre-oxidized after dehydration and drying. Zr with a gradient transition structure is in situ grown on the surface of the Zr-4 zirconium alloy cladding. x O oxide film; the pre-oxidation is carried out in O2, and the pre-oxidation vacuum is controlled to be 5Pa by adjusting the O2 flow rate, and the pre-oxidation time is 30min;
[0046] Step 2: Ar plasma sputtering activation: After cleaning and drying the pre-oxidized Zr-4 zirconium alloy cladding in step 1, place it in a vacuum vapor deposition device with an auxiliary plasma source, and vertically hoist it on the workpiece rack so that it can rotate and revolve synchronously at the same time. The background vacuum is controlled to be 5×10 -3 Pa, the temperature is 300 ° C, and then Ar gas is introduced, the vacuum value in the vacuum vapor deposition equipment is adjusted to 50Pa, the pulse bias voltage is 500V, the duty cycle is 30%, and the Ar plasma generated by Ar gas glow discharge is used for sputtering cleaning for 15 minutes to clean and eliminate dust and other debris adsorbed by static electricity on the surface and activate the surface;
[0047] Step 3, SiC ion sputtering cleaning: reduce the Ar gas flow rate to adjust the vacuum value in the vacuum vapor deposition equipment to 1Pa, turn on the SiC sputtering target source, control the power of the SiC sputtering target source to 8kW, and use the SiC ions generated by the SiC target source sputtering to perform SiC ion sputtering cleaning on the surface of the Zr-4 zirconium alloy cladding after Ar plasma sputtering cleaning in step 2 for 3 minutes under the conditions of a pulse bias of 1000V and a duty cycle of 30%;
[0048] Step 4: Deposition of SiC composite coating: Under the action of low pulse bias, a multi-layer SiC composite coating is alternately deposited on the surface of the Zr-4 zirconium alloy cladding cleaned by SiC ion sputtering in step 3, thereby obtaining a surface with a gradient transition structure Zr x O / SiC multilayer composite coating Zr-4 zirconium alloy cladding; the SiC composite coating deposition comprises the following steps:
[0049] Step 401, preparation of SiC pre-deposition layer: maintaining the SiC sputtering target source on state unchanged, and the power of the SiC sputtering target source is 8kW, reducing the pulse bias voltage to 300V, controlling the duty cycle to 40%, and the vacuum degree to 1Pa, and pre-depositing the SiC pre-deposition layer on the surface of the Zr-4 zirconium alloy cladding cleaned by SiC ion sputtering in step 3 for 5 minutes;
[0050] Step 402, preparation of SiC thickening layer: reducing the pulse bias voltage to 50V, controlling the duty cycle to 40%, and the vacuum degree to 1Pa, depositing the SiC pre-deposition layer on the surface of the Zr-4 zirconium alloy cladding in step 401 for 60 minutes, and preparing a SiC thickening layer with a thickness of 3 μm;
[0051] The SiC pre-deposition layer preparation process in step 401 and the SiC thickening layer preparation process in step 402 were repeated alternately 4 times each to form a SiC composite coating having a 6-layer periodic structure and a total thickness of 15 μm.
[0052] The Zr formed on the surface of the Zr-4 zirconium alloy cladding in this embodiment x The O / SiC multilayer composite coating was placed in a 1210°C high-temperature furnace for 5 minutes and then quickly placed in 10°C cold water. After being taken out, it was found that the surface of the composite coating was intact without defects such as shedding and bulging. The surface SiC composite coating had no cracks, bulging, shedding, etc.
[0053] The Zr formed on the surface of the Zr-4 zirconium alloy cladding in this embodiment x The O / SiC multilayer composite coating was placed in 1200℃ high-temperature steam for 2h and subjected to a steam corrosion test. The results showed that the composite coating was intact on the surface, and the Zr-4 zirconium alloy cladding substrate did not show any oxidation corrosion, indicating that the composite coating had a significant protective effect.
[0054] Example 3
[0055] This embodiment includes the following steps:
[0056] Step 1: Zr x Preparation of O oxide film: The Zr-4 zirconium alloy cladding is pickled and rinsed with deionized water to remove surface oxides and attached pollutants, and then pre-oxidized after dehydration and drying. Zr with a gradient transition structure is in situ grown on the surface of the Zr-4 zirconium alloy cladding.x O oxide film; the pre-oxidation is carried out in O2, and the pre-oxidation vacuum is controlled to be 5Pa by adjusting the O2 flow rate, and the pre-oxidation time is 30min;
[0057] Step 2: Ar plasma sputtering activation: After cleaning and drying the pre-oxidized Zr-4 zirconium alloy cladding in step 1, place it in a vacuum vapor deposition device with an auxiliary plasma source, and vertically hoist it on the workpiece rack so that it can rotate and revolve synchronously at the same time. The background vacuum is controlled to be 5×10 -3 Pa, the temperature is 200 ° C, and then Ar gas is introduced, the vacuum value in the vacuum vapor deposition equipment is adjusted to 3Pa, and the pulse bias is 1500V, the duty cycle is 50%, and the Ar plasma generated by Ar gas glow discharge is used for sputtering cleaning for 7 minutes to clean and eliminate dust and other debris adsorbed by static electricity on the surface and activate the surface;
[0058] Step 3, SiC ion sputtering cleaning: reduce the Ar gas flow rate to adjust the vacuum value in the vacuum vapor deposition equipment to 0.1 Pa, turn on the SiC sputtering target source, control the power of the SiC sputtering target source to 10kW, and use the SiC ions generated by the SiC target source sputtering to perform SiC ion sputtering cleaning on the surface of the Zr-4 zirconium alloy cladding after Ar plasma sputtering cleaning in step 2 for 2 minutes under the conditions of a pulse bias of 1500V and a duty cycle of 50%;
[0059] Step 4: Deposition of SiC composite coating: Under the action of low pulse bias, a multi-layer SiC composite coating is alternately deposited on the surface of the Zr-4 zirconium alloy cladding cleaned by SiC ion sputtering in step 3, thereby obtaining a surface with a gradient transition structure Zr x O / SiC multilayer composite coating Zr-4 zirconium alloy cladding; the SiC composite coating deposition comprises the following steps:
[0060] Step 401, preparation of SiC pre-deposition layer: maintaining the SiC sputtering target source on state unchanged, and the power of the SiC sputtering target source is 10kW, reducing the pulse bias voltage to 500V, controlling the duty cycle to 50%, and the vacuum degree to 0.1Pa, and pre-depositing the SiC pre-deposition layer on the surface of the Zr-4 zirconium alloy cladding cleaned by SiC ion sputtering in step 3 for 10 minutes;
[0061] Step 402, preparation of SiC thickening layer: reducing the pulse bias voltage to 100V, controlling the duty cycle to 50%, the vacuum degree to 0.1Pa, depositing the SiC pre-deposition layer on the surface of the Zr-4 zirconium alloy cladding in step 401 for 30min, and preparing a SiC thickening layer with a thickness of 1μm;
[0062] The SiC pre-deposition layer preparation process in step 401 and the SiC thickening layer preparation process in step 402 were repeated alternately 9 times each to form a SiC composite coating having a 10-layer periodic structure and a total thickness of 10 μm.
[0063] The Zr formed on the surface of the Zr-4 zirconium alloy cladding in this embodiment x The O / SiC multilayer composite coating was placed in a 1210°C high-temperature furnace for 5 minutes and then quickly placed in 10°C cold water. After being taken out, it was found that the surface of the composite coating was intact without defects such as shedding and bulging. The surface SiC composite coating had no cracks, bulging, shedding, etc.
[0064] The Zr formed on the surface of the Zr-4 zirconium alloy cladding in this embodiment x The O / SiC multilayer composite coating was placed in 1200℃ high-temperature steam for 2h and subjected to a steam corrosion test. The results showed that the composite coating was intact on the surface, and the Zr-4 zirconium alloy cladding substrate did not show any oxidation corrosion, indicating that the composite coating had a significant protective effect.
[0065] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x The method for preparing an O / SiC multilayer composite coating is characterized in that: The method comprises the following steps: Step 1: Zr x Preparation of O oxide film: The zirconium-based fuel cladding is surface pickled and rinsed with deionized water to remove surface oxides and attached pollutants, and then pre-oxidized after dehydration and drying. Zr with a gradient transition structure is in situ grown on the surface of the zirconium-based fuel cladding. x O oxide film; Step 2: Ar plasma sputtering activation: Place the pre-oxidized zirconium-based fuel cladding in step 1 in a vacuum vapor deposition device and control the background vacuum to be better than 5×10 -3 Pa, the temperature does not exceed 400 ° C, and then Ar gas is introduced, and Ar plasma generated by Ar gas glow discharge is used for sputtering cleaning to clean and eliminate dust and other debris adsorbed by static electricity on the surface and activate the surface; Step 3, SiC ion sputtering cleaning: Turn on the SiC sputtering target source, and under the action of high pulse bias, use SiC ions generated by the SiC target source to perform SiC ion sputtering cleaning on the surface of the zirconium-based fuel cladding after the Ar plasma sputtering cleaning in step 2; Step 4: Deposition of SiC composite coating: Under the action of low pulse bias, a multi-layer SiC composite coating is alternately deposited on the surface of the zirconium-based fuel cladding cleaned by SiC ion sputtering in step 3, thereby obtaining a surface with a gradient transition structure Zr x Zirconium-based fuel cladding with O / SiC multilayer composite coating.
2. According to claim 1, a zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x The method for preparing an O / SiC multilayer composite coating is characterized in that: The pre-oxidation in step one is carried out in an oxygen-containing atmosphere, or in high-temperature, high-pressure steam. The conditions for pre-oxidation in high-temperature, high-pressure steam are: pre-oxidation for 72 hours under high-temperature steam conditions of 400°C ± 3°C and 10.3MPa ± 0.7MPa in an autoclave.
3. According to claim 1, a zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x The method for preparing an O / SiC multilayer composite coating is characterized in that: During the Ar plasma sputtering cleaning in step 2, Ar gas is used to adjust the vacuum value in the vacuum vapor deposition equipment to 3Pa-50Pa, and the pulse bias voltage is 500V-1500V, the duty cycle is 30%-80%, and the time is 7min-15min.
4. According to claim 1, a zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x The method for preparing an O / SiC multilayer composite coating is characterized in that: The pulse bias voltage of the SiC ion sputtering cleaning in step 3 is 500V to 1000V, and the time is 2min to 5min.
5. According to claim 1, a zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x The method for preparing an O / SiC multilayer composite coating is characterized in that: The SiC composite coating deposition in step 4 includes the following steps: Step 401, preparation of SiC pre-deposition layer: maintaining the on state of SiC sputtering target source unchanged, reducing the pulse bias voltage, and preparing SiC pre-deposition layer on the surface of zirconium-based fuel cladding cleaned by SiC ion sputtering in step 3; Step 402 , preparation of SiC thickening layer: reducing the pulse bias voltage, and depositing a SiC thickening layer on the surface of the SiC pre-deposition layer of the zirconium-based fuel cladding in step 401 .
6. The zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr according to claim 5 x The method for preparing an O / SiC multilayer composite coating is characterized in that: The pulse bias voltage used in preparing the SiC pre-deposition layer in step 401 is 300V~500V, the time is 5min~10min, and the vacuum degree is 0.1Pa~1Pa; the pulse bias voltage used in preparing the SiC thickening layer in step 402 is 50V~100V, and the vacuum degree is 0.1Pa~1Pa.
7. The zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr according to claim 5 x The method for preparing an O / SiC multilayer composite coating is characterized in that: The SiC pre-deposition layer preparation process in step 401 and the SiC thickening layer preparation process in step 402 are repeated alternately for multiple times to form a multi-layered SiC composite coating.
8. The zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr according to claim 1 x The method for preparing an O / SiC multilayer composite coating is characterized in that: An auxiliary plasma source is added to the vacuum vapor deposition equipment described in step 2.
9. A zirconium-based fuel cladding surface corrosion-resistant interface integrated Zr x O / SiC multilayer composite coating, characterized in that: The method is prepared by any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing oxidation film standard component on surface of zirconium alloy cladding pipe
CN105420787A
Method for preparing composite ceramic coating on zirconium alloy cladding
CN109355611A
Preparation method of zirconium alloy cladding surface high-temperature-corrosion-resistant composite coating
CN114232052A
METHOD OF MANUFACTURING A SiC COMPOSITE FUEL CLADDING WITH INNER Zr ALLOY LINER
US20170365364A1